Analisis Perilaku Hidup Bersih dan Sehat Tatanan Rumah Tangga di Wilayah Kerja Puskesmas Tanjung Agung - Elwan Candra; Lilis Suryani; Dewi Suryanti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Clean and healthy living behavior (PHBS) must start from the household and family structure, because a healthy household is an asset and capital for future development that needs to be maintained, improved and protected. This study aims to determine what factors are associated with clean and healthy living behavior in household arrangements in the Tanjung Agung Public Health Center, Baturaja Barat District, OKU Regency in 2022. This study used a quantitative method with a cross sectional design. The population in this study is the head of the family (KK) in the Tanjung Agung Public Health Center, Baturaja Barat District, OKU Regency in 2021. The sampling method in this study uses a purposive sampling technique. The number of samples in this study were 263 respondents. Data collection by using a questionnaire. The results of statistical test analysis using the Chi-Square test showed that there was a significant relationship (p value < 0.05), education (p value 0.027), knowledge (p value 0.000), attitude ((p value 0.000), the role of officers (p value 0.000) and facilities and infrastructure (p value 0.005). From the results of multivariate analysis, it was found that the dominant factor on clean and healthy living behavior in household arrangements in the Tanjung Agung Health Center work area, Baturaja Barat District, OKU Regency in 2022, namely the role of officers (p value 0.000) (OR 8.302). From the results of this study, it is hoped that health workers will provide counseling to the community and provide understanding